Relationship between personality traits and organizational commitment: a case study of Pejabat Residen Bahagian Kuching, Sarawak/ Olivia Sutee Jugie - Jugie, Olivia Sutee (2016)
The main purpose of this study is to examine the relationship between personality traits and organizational commitment among employees in Pejabat Residen Bahagian Kuching. The instrument that was used to collect the data was questionnaires. All of the 40 employees or respondents answered the questionnaires. The data was analysed by using Statistical Package for Social Science Software (SPSS) version 20. Pearson Correlation was performed on the data in order to determine whether there is relationship between personality traits and organizational commitment. The findings show that there is a strong relationship between both variables. The correlation value shows that personality traits have strong relationship with organizational commitment (r = .600 and p<0.01). The researcher recommends that the future research should be expanded to other location rather than in Kuching only.